2014
DOI: 10.7150/jca.7668
|View full text |Cite
|
Sign up to set email alerts
|

A Majority of Low (1-10%) ER Positive Breast Cancers Behave Like Hormone Receptor Negative Tumors

Abstract: Background: The 2010 guidelines by ASCO-CAP have mandated that breast cancer specimens with ≥1% positively staining cells by immunohistochemistry should be considered Estrogen Receptor (ER) positive. This has led to a subclass of low-ER positive (1-10%) breast cancers. We have examined the biology and clinical behavior of these low ER staining tumors.Methods: We have developed a probabilistic score of the “ER-positivity” by quantitative estimation of ER related gene transcripts from FFPE specimens. Immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 34 publications
5
96
2
3
Order By: Relevance
“…7 Clinically the majority of these tumours were also found to behave more like ER negative tumours. 8 While the binary scoring system may be adequate, the percentage score may provide additional information in treatment decision making, as ER and/or PR levels have been demonstrated to be associated with patient outcome. Staining of >50% of tumour cells was viewed as indicating highly endocrine-responsive tumours.…”
Section: Ihc Scoring Systemmentioning
confidence: 99%
“…7 Clinically the majority of these tumours were also found to behave more like ER negative tumours. 8 While the binary scoring system may be adequate, the percentage score may provide additional information in treatment decision making, as ER and/or PR levels have been demonstrated to be associated with patient outcome. Staining of >50% of tumour cells was viewed as indicating highly endocrine-responsive tumours.…”
Section: Ihc Scoring Systemmentioning
confidence: 99%
“…For example, in ER+ tumors, not all cells express the receptor. Clinically, ER+ breast cancers can be qualified as such even if only 1% of cells express detectable levels of ER protein, though some low-expressing tumors may behave as ER-negative tumors in response to targeted therapies [29,30]. Similarly, HER2+ tumors can show regional variation in expression by immunohistochemistry and copy number per cell by fluorescence in situ hybridization, with positivity clinically defined as 10% of cells positive (CAP Guidelines) [31,32,12].…”
Section: Introductionmentioning
confidence: 99%
“…While the low cut-off setting is clinically justifiable to administer non-toxic treatment for a life-threatening disease, it also disposes for overtreatment. Indeed, the biology of tumours with low ER expression often resembles ER-negative tumours [68,69] and numerous studies have confirmed that level of tumour ER expression is associated with the likelihood of endocrine responsiveness. In context of response to AIs, this was most clearly shown in the P024 trial which compared neo-adjuvant Letrozole and Tamoxifen [61].…”
Section: Oestrogen Receptormentioning
confidence: 99%
“…On one side, there is a relatively small group (up to ~20 %) of low risk patients with excellent prognosis, usually ER-rich, which do not need addition of cytotoxic therapy to adjuvant treatment [109,125,126,132]. On the other side of the range, tests may identify a group of ER+ve tumours with low expression of ER (up to ~10 % of ER+ve tumours) [68,69] and/or inconsistent with luminal phenotype [122]. Albeit these high-risk tumours are associated with poor response rates, some of these ER+ve tumours still may respond to AI treatment.…”
Section: Signatures To Predict Neo-adjuvant Response To Aismentioning
confidence: 99%
See 1 more Smart Citation